Clinical Significance of Novel Neutrophil-Based Biomarkers in the Diagnosis and Prediction of Response to Infliximab Therapy in Crohn’s Disease - Zhou, Zhou; Zhang, Yinghui; Yang, Xue; Pan, Yan; Li, Liangping; Gao, Caiping; He, Chong (Frontiers in Immunology, 2022)
With the increasing incidence and prevalence, Crohn’s disease (CD) has become one of the most challenging diseases in both diagnosis and treatment of gastroenterology. Evaluation of the disease activity and mucosal healing guides clinical decisions regarding subsequent therapy for CD. In this study, we enrolled a total of 144 patients with CD and 239 healthy controls were enrolled. Clinical characteristics and laboratory parameters of enrolled subjects were retrieved from the electronic medical record database of our hospital. Serum cytokine levels were measured by enzyme-linked immunosorbent assay (ELISA). Mucosa expression levels of inflammatory agents were measured by quantitative RT-PCR (qRT-PCR). We identified two neutrophil-based indexes, the neutrophil-to-albumin ratio (NAR) and neutrophil-to-bilirubin ratio (NBR), both of which had not yet been explored in CD or UC. NAR and NBR were significantly increased in patients with CD compared to those in healthy controls, and both indexes showed significantly positive correlations with CD activity and inflammatory load. In note, NAR and NBR showed better performance than blood neutrophil percentage, serum albumin, or bilirubin alone in these scenarios. More importantly, both NAR and NBR discriminated CD patients who completely or partially responded to infliximab (IFX) induction therapy from those with primary non-response. Our observations suggest that NAR and NBR may serve as promising biomarkers in the diagnosis and prediction of response to IFX therapy in CD.